2012
DOI: 10.1111/j.1365-2125.2012.04164.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Δ9‐tetrahydrocannabinol formulation Namisol® has beneficial pharmacokinetics and promising pharmacodynamic effects

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Cannabis based medicines are registered as a treatment for various indications, such as pain and spasms in multiple sclerosis (MS) patients, and anorexia and nausea in patients with HIV or receiving cancer treatment. • the pharmacokinetics of the various administration routes of cannabis and cannabis based medicines are variable and dosing is hard to regulate. WHAT THIS STUDY ADDS • Namisol is a new tablet containing pure THC (>98%) that has a beneficial pharmacokinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 37 publications
8
61
0
Order By: Relevance
“…Each block contained two drug periods: THC for three consecutive days, followed by placebo (or vice versa) and separated by a fourday-washout period. As the pharmacodynamic effects of oral THC occurred within 1-2 hours after administration in a previous phase I study (17), a study period of three days was expected to be sufficient to evaluate the acute effects of THC on behavior. The duration of the washout period of four days was determined based on the terminal half lives of THC (mean 71.9 min) and its active metabolite 11-OH-THC (mean 196 min) after oral administration of 5mg THC in the same study (17).…”
Section: Methodsmentioning
confidence: 99%
“…Each block contained two drug periods: THC for three consecutive days, followed by placebo (or vice versa) and separated by a fourday-washout period. As the pharmacodynamic effects of oral THC occurred within 1-2 hours after administration in a previous phase I study (17), a study period of three days was expected to be sufficient to evaluate the acute effects of THC on behavior. The duration of the washout period of four days was determined based on the terminal half lives of THC (mean 71.9 min) and its active metabolite 11-OH-THC (mean 196 min) after oral administration of 5mg THC in the same study (17).…”
Section: Methodsmentioning
confidence: 99%
“…The first dataset contains 13 subjects and a total of 243 THC plasma concentrations from trial 0828 at the CHDR, as described by Klumpers et al [27]. There were six healthy male subjects and seven healthy female subjects included in the trial, all were mild cannabis users for at least 1 year (cannabis use no more than once a week) who were given an oral formulation of 5, 6.5, or 8 mg THC called Namisol Ò .…”
Section: Datasets For Model Developmentmentioning
confidence: 99%
“…Earlier reports of sublingual administration have indicated that THC is effectively absorbed by this route (26 -28). For example, sublingual administration of a crushed Namisol w tablet (oral formulation containing 5 mg of THC) to 13 subjects resulted in a maximum plasma concentration (C max ) of 2.3 ng/mL of THC with a peak time of 74.5 min (T max ) (29).…”
Section: Discussionmentioning
confidence: 99%